Supramolecular chiral self-assembly and supercoiling behavior of carrageenans at varying salt conditions. Issue 39 (18th September 2015) - Schefer, Larissa; Adamcik, Jozef; Diener, Michael; Mezzenga, Raffaele
Abstract : The supramolecula chiral amplification and supercoiling behavior of kappa and iota carrageenan polymers are resolved by single molecule AFM imaging. Abstract : The self-assembly of anionic kappa and iota carrageenan polysaccharides in the presence of NaCl, KCl and CaCl2 is studied by high-resolution atomic force microscopy (AFM). A hierarchical supramolecular chirality amplification over various length scales is observed upon the addition of KCl, whereas in the presence of NaCl and CaCl2 the chains undergo solely a coil–helix transition with stiff kappa carrageenan and more flexible iota carrageenan helical conformations.